Joint association of frailty and depression with new-onset digestive disease among elderly Chinese population - Zhang, Fan; Xiong, Yu-Jun; Meng, Xiang-Da; Lv, Tian; Yang, Du-Juan (Frontiers in Nutrition, 2025)
BackgroundDigestive diseases impose a substantial global health burden, yet the joint impact of frailty and depression on their incidence remains underexplored.MethodsThis cohort study analyzed 5,506 adults aged ≥ 65 years from the China Health and Retirement Longitudinal Study (2011–2018). Participants with baseline digestive diseases or missing data were excluded. Cox proportional hazards models assessed associations, while mediation analysis evaluated bidirectional roles of the frailty index (FI) and 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) in new-onset digestive diseases.ResultsOver 7 years, 988 participants developed digestive diseases. Frailty (HR = 1.66, p < 0.001) and depression (HR = 1.62, p < 0.001) independently increased risk, with the highest hazard in comorbid cases (HR = 2.16, p < 0.001). Frailty mediated 30.5% of depression’s effect, while depression mediated 45.2% of frailty’s impact (p < 0.05). No multiplicative or additive interaction was observed.ConclusionFrailty and depression synergistically elevate digestive disease risk in aging populations, with bidirectional mediation underscoring their interdependence. Integrated interventions targeting mental health and geriatric vulnerability may mitigate disease burden.